Ethical issues and best practice in clinically based genomic research: Exeter Stakeholders Meeting Report. Issue 11 (27th September 2016) - Carrieri, D; Bewshea, C; Walker, G; Ahmad, T; Bowen, W; Hall, A; Kelly, S
Abstract : Current guidelines on consenting individuals to participate in genomic research are diverse. This creates problems for participants and also for researchers, particularly for clinicians who provide both clinical care and research to their patients. A group of 14 stakeholders met on 7 October 2015 in Exeter to discuss the ethical issues and the best practice arising in clinically based genomic research, with particular emphasis on the issue of returning results to study participants/patients in light of research findings affecting research and clinical practices. The group was deliberately multidisciplinary to ensure that a diversity of views was represented. This report outlines the main ethical issues, areas of best practice and principles underlying ethical clinically based genomic research discussed during the meeting. The main point emerging from the discussion is that ethical principles, rather than being formulaic, should guide researchers/clinicians to identify who the main stakeholders are to consult with for a specific project and to incorporate their voices/views strategically throughout the lifecycle of each project. We believe that the mix of principles and practical guidelines outlined in this report can contribute to current debates on how to conduct ethical clinically based genomic research.